Required skills and leadership characteristics of a modern manager in tourism and hospitality - Konstantin Petkovski (UTMS Journal of Economics, 2012)
This research was conducted on 209 respondents in the field of tourism and hospitality. The aim of the research was to determine the necessary leadership characteristics and skills of a modern tourism and hospitality manager, as leader of the organization or team in it. For the purposes of the survey questionnaire was used to ascertain the views and opinions of the respondents in terms of categories: psychological characteristics, personality, social characteristics, skills for establishing good interpersonal relations, intelligence and ability and characteristics related to work relations. As a result of the survey the following important characteristics and skills were determined: energy, mobility, self-confidence, originality and creativity, communication skills and ability to set and track goals.
Keywords: L83; J53; 330; leadership; manager in tourism and hospitality; research; communication; characteristics and skills